2002
DOI: 10.1081/ceh-100108711
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Lorenz Scatterplots With Frequency-Domain Heart Rate Variability

Abstract: Heart rate (HR) variability is important with respect to disease prognosis and the effects of drugs. Lorenz scatterplots provide a simple way to evaluate HR variability visually. The relation of Lorenz scatterplots to frequency-domain HR variability was examined in 75 Holter recordings and in simulated HR trends. The length of Lorenz scatterplots was double-exponentially correlated with total frequency and very-low frequency powers, with correlation coefficients (r) of 0.88. The width of Lorenz scatterplots wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…It has often been assumed that the different LP shapes are due to variations in efferent sympathetic and parasympathetic activity, 8–10 and conclusions have been drawn as to the prognostic value of the LP method in cardiac risk stratification 4–10 . However, the contribution of arrhythmias to the LP shapes has not been adequately considered.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has often been assumed that the different LP shapes are due to variations in efferent sympathetic and parasympathetic activity, 8–10 and conclusions have been drawn as to the prognostic value of the LP method in cardiac risk stratification 4–10 . However, the contribution of arrhythmias to the LP shapes has not been adequately considered.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous clinical studies 1–12 have demonstrated that an interval series obtained during sinus rhythm with well‐preserved heart rate variability will produce a cluster of points grouped around the bisector with a club like appearance. According to accepted nomenclature 4–7 such a pattern is usually referred to as a “comet” shape (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations